Práticas de educação, parceria escola – comunidade e desenvolvimento sustentável: uma análise na primeira escola pública 100% sustentável da América Latina - Silveira, Gláucia Espinosa da (2021)
The challenge of sustainable development is difficult and complex, requiring new partnerships through cooperative relationships to establish a culture of sustainability. For that, it is also necessary to develop Education for Sustainable Development practices that play a fundamental role since their assumptions and values are disseminated in all 17 Sustainable Development Goals. Thus, based on the capacity that education has to interact with the other objectives and goals of the 2030 Agenda, it becomes a crucial factor for the implementation of the SDGs as a mechanism that drives sustainable development as well as bringing new paradigms to the educational process. The present study aimed to analyze the contribution of the education practices of a sustainable school and the school-community partnership to the achievement of the objectives of sustainable development. The research had a qualitative approach, the method chosen was the case study, various data collection techniques were used, such as documentary research, observation, testimonies, visual materials, and semi-structured interviews with directors, teachers, community, and government members in order to triangulate the data. The results showed that the educational practices of the Sustainable School are based on the characteristics of Education for Sustainable Development; The school-community partnership is effective, although there is still room for progress; The main actions that contribute to the achievement of the SDGs are related to the Sustainability Principle of the School of Food Production (SDG1), school activity of Food Production (SDG2), pedagogical strategies of the Una Escuela Sustentable Project (SDG4), Sustainability Principle of the Wastewater Treatment School (SDG6), Sustainability Principle of the Waste Reuse School (SDG12), Sustainability Principle of the Thermal Conditioning School (SDG13), studies on fauna and flora, forest and wildlife conservation (SDG 15), solar photovoltaic systems (SDG7), bio construction model (SDG11), School Pedagogical Project (SDG16) and school construction project (SDG17). In view of the evidence that the school develops Education for Sustainable Development practices and also has effective partnerships with the community, significant contributions to the achievement of the SDGs were identified, by using the full potential of the community, the school can maximize its influence and further stimulate plus the region's Sustainable Development.